2020
DOI: 10.1002/ange.202005114
|View full text |Cite
|
Sign up to set email alerts
|

Polyesters by a Radical Pathway: Rationalization of the Cyclic Ketene Acetal Efficiency

Abstract: Radical ring‐opening polymerization (rROP) of cyclic ketene acetals (CKAs) combines the advantages of both ring‐opening polymerization and radical polymerization thereby allowing the robust production of polyesters coupled with the mild polymerization conditions of a radical process. rROP was recently rejuvenated by the possibility to copolymerize CKAs with classic vinyl monomers leading to the insertion of cleavable functionality into a vinyl‐based copolymer backbone and thus imparting (bio)degradability. Suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…To have a better understanding of this phenomenon, DFT calculations were performed to determine the enthalpies of reaction as well as the activation energies of i) the addition of alkyls radicals onto the thionolactone functionality and ii) the β-scission of the intermediate radical that either leads to thioester and a second released alkyl radical or gives back the thionolactone and the propagating vinyl macroradical (Scheme 3).To perform such theoretical study, we choose the UB3LYP/6-31G(d) level of theory due to the large number of atoms that are involved in the system. Moreover we already showed that this level of theory allowed us to have a good understanding of the homopolymerization of CKA 19 or the copolymerization behavior of CKA with various vinyl monomers. 20,21 Scheme 3.…”
Section: Theoretical Considerationsmentioning
confidence: 93%
See 3 more Smart Citations
“…To have a better understanding of this phenomenon, DFT calculations were performed to determine the enthalpies of reaction as well as the activation energies of i) the addition of alkyls radicals onto the thionolactone functionality and ii) the β-scission of the intermediate radical that either leads to thioester and a second released alkyl radical or gives back the thionolactone and the propagating vinyl macroradical (Scheme 3).To perform such theoretical study, we choose the UB3LYP/6-31G(d) level of theory due to the large number of atoms that are involved in the system. Moreover we already showed that this level of theory allowed us to have a good understanding of the homopolymerization of CKA 19 or the copolymerization behavior of CKA with various vinyl monomers. 20,21 Scheme 3.…”
Section: Theoretical Considerationsmentioning
confidence: 93%
“…led to similar results but with increased computational time. 19,20,22 The results of the calculations are gathered in Table 2. We can first observe that the β-scission reaction of the radical intermediate is not affected by the nature of the radical adduct since both enthalpies of reaction ΔHr and activation energies are rather similar (close to -23 kJ mol -1 for ΔHr and close to 60 kJ mol -1 for the Ea,β).…”
Section: Theoretical Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The design of biodegradable and bio-based plastics is an appropriate, ecoefficient approach to enhance the environmental quality of many products. [113][114][115][116] Up until now, many biodegradable plastics still struggle to compete with petroleum-based bulk products especially in terms of cost-competitiveness and thermo-mechanical properties. To increase their commercial scale-up and competitiveness while still maintaining biodegradable properties, these type of polymers are generally mixed with organic/inorganic fillers.…”
Section: Macro-scale Challenges For Chemical Modification Of Starch Polymersmentioning
confidence: 99%